CREB-Binding Protein Is a Mediator of Neuroblastoma Cell Death Induced By the Histone Deacetylase Inhibitor Trichostatin A - Chitra Subramanian (Neoplasia: An International Journal for Oncology Research, 2007)
The cytotoxic mechanism of the histone deacetylase inhibitor (HDACI) Trichostatin A (TSA) was explored in a neuroblastoma (NB) model. TSA induces cell death in neuroblastic-type NB cells by increasing the acetylation of Ku70, a Bax-binding protein. Ku70 acetylation causes Bax release and activation, triggering cell death. This response to TSA depends on the CREB-binding protein (CBP) acetylating Ku70. TSA-induced cell death response correlates with CBP expression. In stromaltype NB cell lines with low levels of CBP and relative resistance to TSA, increasing CBP expression disrupts Bax-Ku70 binding and sensitizes them to TSA. Reducing CBP expression in neuroblastic cell types causes resistance. Cytotoxic response to TSA is Baxdependent. Interestingly, depleting NB cells of Ku70 also triggers Bax-dependent cell death, suggesting that conditions that leave Bax unbound to Ku70 result in cell death. We also show that CBP, Ku70, and Bax are expressed in human NB tumors and that CBP expression varies across cell types comprising these tumors, with the highest expression observed in neuroblastic elements. Together, these results demonstrate that CBP, Bax, and Ku70 contribute to a therapeutic response to TSA against NB and identify the possibility of using these proteins to predict clinical responsiveness to HDACI treatment.